2022
DOI: 10.1007/s00246-022-02851-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Complications Associated with COVID-19, MIS-C, and mRNA COVID-19 Vaccination

Abstract: The COVID-19 vaccine is now approved for individuals greater than 5 years of age, but vaccination rates remain lower than expected in the pediatric age group. Misinformation and widespread reporting of vaccine-related myocarditis are contributing to vaccine hesitancy. When compared to severe cardiac complications that are associated with COVID-19, vaccine-related myocarditis has a milder presentation, is easily treated, and has a good prognosis. Acute COVID-19 has been associated with higher rates of myocardit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Currently, long-term cardiovascular effects of MIS-C are not known yet. Patients have both acute and subacute complications and cardiovascular manifestations vary from mild to severe [ 63 ]. Thus, the results of a systematic review with meta-analysis, where there were 27 studies and it included 917 patients with MIS-C, the average age was 9.3 years old (95% confidence interval (CI), 8.4–10.1) [ 64 ].…”
Section: Multisystem Inflammatory Syndrome Associated With Covid-19 I...mentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, long-term cardiovascular effects of MIS-C are not known yet. Patients have both acute and subacute complications and cardiovascular manifestations vary from mild to severe [ 63 ]. Thus, the results of a systematic review with meta-analysis, where there were 27 studies and it included 917 patients with MIS-C, the average age was 9.3 years old (95% confidence interval (CI), 8.4–10.1) [ 64 ].…”
Section: Multisystem Inflammatory Syndrome Associated With Covid-19 I...mentioning
confidence: 99%
“…It should be noted that MIS-C can look like Kawasaki disease, based on clinical and laboratory signs. However, the high frequency of damage is typical for MIS-C in African Americans and Latin Americans and the prevalence in older age (the average age is 9) and, probably, a higher incidence of myocarditis, an elevation of troponin, ventricular dysfunction, and need for vasopressor drugs [ 63 ].…”
Section: Multisystem Inflammatory Syndrome Associated With Covid-19 I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Anakinra, which has immunosuppressive activity by blocking interleukin-1 receptors, has also been shown to be effective in patients with MIS-CH [14]. A number of researchers consider the use of metipred in the early stages to block secondary inflammatory processes in the treatment of children with multisystem inflammatory syndrome by strictly controlling the concentration of CRP and leukocytes in the blood [15]. Also W.J.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the milder clinical course compared to classic MYO and MIS-C MYO, strong pharmacologic support is only rarely required in patients with COVID-19 vaccine-related MYO. Use of non-steroidal anti-inflammatory drugs, immune globulin (IVIG), and steroids is not common ( 48 ) and remains controversial ( 49 ). A pediatric study comparing drug use in patients with viral MYO, MIS-C MYO and vaccine-related MYO has shown that intravenous immunoglobulin (IVIG) and steroids were frequently used in patients with classic MYO and MIS-C MYO but in only one and in none of the 9 patients with previous COVID-19 immunization ( 50 ).…”
Section: Clinical Characteristics and Outcome Of Myocarditis Associat...mentioning
confidence: 99%